Three Birds with One Stone: Empower, Include, and Sustain the Emirati Community Program; Kayani - Gaad, Eman (2017)
The paper presents the findings of a nationally funded project to support the inclusion of learners with disabilities in government schools in the United Arab Emirates (UAE). The project was known as “Kayani” which means “my identity” in Arabic. The project helped at the same time to enable non-working Emirati women to gain knowledge and skills needed to become teacher assistants across the UAE. The project is changing those nonworking individuals into productive employees who contribute to the development of their nation and support the inclusive education policy that the UAE is adopting following the ratification of United Nation’s Convention on the Rights of Persons with Disabilities (UNCRPD). The paper examines to what extent the aims of the programme were achieved using several methods including quantitative and qualitative to reach the findings. Such findings are presented with recommendations for future practice.